Manajemen Pengetahuan di Divisi Engineering PT. SKF Indonesia - Kusuma, Hansen; Priyandari, Yusuf (Performa: Media Ilmiah Teknik Industri, 2017)
Effective and efficient organization is an organization that can benefit form the wealth of knowledge they have and also learn from those experienced before. Identification of existing knowledge in organization is urgently needed before the knowledge is managed with knowledge management. This study used qualitative análisis methods from the approach Nonaka’s model and Alavi’s cycle. Alavi cycle is used to identify existing knowledge cycle while the Nonaka’s model is used to identify th process of the knowledge formation. After the research is done, then it can be grouped into three business processes conducted in the Division, the forms of knowledge that already exists and the four domains of knowledge. Four of these knowledge domains identified more related to process creation, storage, transfer and application. The process of the creation of the four domains of knowledge are identified more related to the process of socialization, externalization, combination, internalization